A retrospective on Culture's Consequences: The 35-year journey. Issue 1 (January 2017) - Kirkman, Bradley; Lowe, Kevin; Gibson, Cristina
Abstract Our 2006Journal of International Business Studies article, "A Quarter Century ofCulture's Consequences : A Review of the Empirical Research Incorporating Hofstede's Cultural Values Framework, " provided a comprehensive review of 180 empirical journal articles and edited volume chapters published between 1980 and June 2002 that incorporated Hofstede's cross-cultural values framework. We examined empirical research that positioned culture as either a main or moderating effect. The review attempted to make sense of the almost quarter century of research examining the impact of culture at the individual, group/organization, and country levels. In the present commentary, we provide: (a) a summary of the progress that has been made in the intervening decade, and most importantly, (b) a new set of recommendations for the next decade to guide those wishing to study the role of national culture in organizations. Résumé Notre article de 2006 publié dansJournal of International Business Studies, "A Quarter Century ofCulture's Consequences : A Review of the Empirical Research Incorporating Hofstede's Cultural Values Framework, " a proposé une analyse complète de 180 articles de revues et chapitres d'ouvrages collectifs empiriques publiés entre 1980 et juin 2002 qui ont intégré le cadre théorique des valeurs cross-culturelles de Hofstede. Nous avons examiné les recherches empiriques qui considéraient la culture comme un effet principal ou modéré. L'analyse visait à donner du sens à la recherche de près d'un quart de siècle, étudiant l'impact de la culture aux niveaux individuel, des groupes/organisationnel et des pays. Dans le présent commentaire, nous livrons : (a) une synthèse du progrès qui a été réalisé durant la période d'étude et, de manière plus importante, (b) un nouvel ensemble de recommandations pour la prochaine décennie afin de guider ceux qui souhaitent étudier le rôle de la culture nationale dans les organisations. Resumen Nuestro artículo del 2006 en elJournal of International Business Studies, "Un cuarto de siglo de las Consecuencias de la Cultura: Una revisión de la Investigación Empírica Incorporado el Marco de Valores Culturales de Hofstede " proporcionó una revisión exhaustiva de 180 artículos empíricos y capítulos en volúmenes editados publicados entre 1980 y junio del 2002 que incorporaban el marco de valores culturales. Examinamos la investigación empírica que sitúo la cultural ya sea como efecto principal o moderador. La revisión intentó dar sentido del casi cuarto de siglo de investigación examinando el impacto de la cultura en los niveles individual, grupo/organización, y país. En este presente comentario, damos: (a) un resumen del progreso que se ha hecho una década después, y lo más importante, (b) un nuevo conjunto de recomendaciones para la próxima década para guiar a quienes deseen estudiar el rol de la cultura nacional en las organizaciones. Resumo Nosso artigo de 2006 doJournal of International Business Studies intitulado, "A Quarter Century ofCulture's Consequences : A Review of the Empirical Research Incorporating Hofstede's Cultural Values Framework" forneceu uma revisão abrangente de 180 artigos científicos empíricos e capítulos editados publicados entre 1980 e Junho de 2002, que incorporaram a estrutura de valores interculturais de Hofstede. Nós examinamos a pesquisa empírica que posicionou cultura como o efeito principal ou moderador. A revisão tentou dar sentido a quase um quarto de século de pesquisas examinando o impacto da cultura nos níveis individual, grupo/organizacional e nacional. No presente comentário, nós fornecemos: (A) um resumo do progresso que tem sido feito na década, e mais importante, (B) um novo conjunto de recomendações para a próxima década para orientar aqueles que desejam estudar o papel da cultura nacional nas organizações. 概要 我们2006年的国际商务研究杂志 文章, "文化的后果的四分之一世纪:运用霍夫斯泰德文化价值观框架的实证研究综述", 对1980年至2002年6月间发表的180篇运用了霍夫斯泰德跨文化价值观框架的实证研究期刊文章和书章进行了全面的综述。我们审查了将文化定位于主要作用或者调节作用的实证研究。该综述试图解读在个人、团体/组织、和国家层面上近四分之一世纪的调查文化影响力的研究。在本评论中, 我们提供:a)对其间十年中取得进展的总结, 最重要的是, (b)针对下个十年的一组新的建议, 以指导对国家文化在组织里的作用的研究。